2020
DOI: 10.7861/fhj.2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive hospital agile preparedness (CHAPs) tool for pandemic preparedness, based on the COVID-19 experience

Abstract: COVID-19 presents an unprecedented challenge to hospitals and the systems in which they operate. The primary exponential surge of COVID-19 cases is arguably the most devastating event a hospital will face. In some countries, these surges during the initial outbreak of the disease have resulted in hospitals suffering from significant resource strain, leading to excess patient mortality and negatively impacting staff wellbeing. As experience builds in managing these surges, it has become evident that agile, tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Within six weeks the number of confirmed cases reached 50 and the working pattern of medical doctors underwent a radical remodelling in response to the anticipated surge in admissions as the pandemic ensued over the coming weeks. 1 Within 24 hours, individual medical speciality teams were replaced with one united workforce consisting of 160 junior doctors and consultants to provide 24-hour cover for acute medical admissions and medical wards, for which COVID-19 was predicted to encompass the bulk of the workload. Specialists in dermatology, haematology, histopathology, immunology, neurology and ophthalmology joined general medical doctors to supplement the workforce on the medical 'super rota'.…”
Section: Responding To the Pandemic And Identification Of Educationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Within six weeks the number of confirmed cases reached 50 and the working pattern of medical doctors underwent a radical remodelling in response to the anticipated surge in admissions as the pandemic ensued over the coming weeks. 1 Within 24 hours, individual medical speciality teams were replaced with one united workforce consisting of 160 junior doctors and consultants to provide 24-hour cover for acute medical admissions and medical wards, for which COVID-19 was predicted to encompass the bulk of the workload. Specialists in dermatology, haematology, histopathology, immunology, neurology and ophthalmology joined general medical doctors to supplement the workforce on the medical 'super rota'.…”
Section: Responding To the Pandemic And Identification Of Educationalmentioning
confidence: 99%
“…Following redeployment, many doctors were now working outside both their field of expertise and their comfort zone. To meet the challenges of this rapid change in the architecture of the workforce, provision of appropriate teaching and training was immediately identified as a priority, 1 and an education faculty was established as part of the COVID-19 Medical Task Force. The objective of the faculty was to rapidly develop and implement an education programme to increase the preparedness of healthcare professionals involved in the COVID-19 response.…”
Section: Responding To the Pandemic And Identification Of Educationalmentioning
confidence: 99%
“…It is unsurprising, therefore, that while comprehensive Pandemic Preparedness Tools (Adelaja et al 2020) all incorporate specific elements designed to support the psychological well-being of healthcare staff, it appears reasonable to assert that additional support structures or tools have not been the experience of clinicians working throughout the pandemic. Indeed, a recent survey by the British Medical Association reported that 40% of the 6650 respondents indicated a worsening in their mental health status compared to pre-pandemic (Rimmer, 2020), with 10% describing their mental health as much worse.…”
Section: Self-carementioning
confidence: 99%
“…As the ongoing pandemic monopolizes human and nancial resources, operational transformation can be challenging for hospitals (Emanuel et al, 2020;Legido-Quigley et al, 2020). Early in the pandemic, hospitals contended with a lack of empirical information regarding the pathophysiology, transmission, and treatment of COVID-19; however, rapidly evolving scienti c literature, real-world data, and shared best practices helped inform on the clinical management of patients and e cient work ow strategies for various medical specialities (Brethauer et ), hospitals will often rely on generic plans that focus on localized, single-event disasters that are not designed for protracted outcomes (Zoutman et al, 2010) and may not address various administrative barriers that are required for operationalizing a successful response (Adelaja et al, 2020; Burgansky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%